APLIKASI MODEL REGRESI SPASIAL UNTUK PEMODELAN ANGKA PARTISIPASI MURNI JENJANG PENDIDIKAN SMA SEDERAJAT DI PROVINSI JAWA TENGAH - Restu Dewi Kusumo Astuti; Hasbi Yasin; Sugito Sugito (Jurnal Gaussian, 2013)
Net Enrollment Ratio (NER) is an  instrument to measure education rate. But NER rate of Senior High School in Central Java Province is only 47,34 %. This study discuss about regression model of factors which influence NER of Senior High School for Central Java province considering  spatial effects for each regency  in Central Java province. The examination of spatial effects shows that there is spatial dependence in response variable so this study is developed by using Spatial Autoregressive Model (SAR). The methods for estimating the parameter are   Ordinary Least Square and Maximum Likelihood Estimation. The result of this study shows that the average number of household members has significant spatial effect for NER rate of Senior High School in Central Java Province. From the comparison AIC value, it was found that SAR model is better to analyze NER rate of Senior High School in Central Java province than classic one.